The Role of Notes to the Financial Statements in Communicating Local Governments’ Non-Financial Performance to Stakeholders - bertha beloan; Sudirman; Nirwana; Aini Indrijawati (Journal of Accounting, Economics, and Business Education, 2026)
This study examines the role of Notes to Financial Statements (CaLK) in conveying the non-financial performance of local governments to stakeholders, utilizing the 2023 Regional Government Financial Report (LKPD) of Makassar City as a case study. The research employs a qualitative descriptive method through documentation and content analysis of the CaLK. The results show that the CaLK of Makassar City's 2023 LKPD has adequately disclosed macroeconomic and social indicators as non-financial performance, including a poverty rate of 5.07%, an open unemployment rate of 10.60%, a Gini ratio of 0.387, a Human Development Index of 84.85, an economic growth rate of 5.31%, and an inflation rate of 2.49%. However, while these indicators are presented with comparative data, the CaLK does not provide an adequate narrative explaining the causal mechanisms by which local fiscal policy contributed to these outcomes, notably the absence of any link between the decline in inflation and specific APBD programs such as subsidized market operations or TPID coordination efforts. The integration of financial realization narratives and socioeconomic performance indicators thus remains partial and procedural. CaLK has not fully served as a strategic communication instrument for non-expert stakeholders, though it demonstrates significant potential as a bridge between fiscal policy and its social impact on the community.